PENGARUH MODEL PEMBELAJARAN QUANTUM DENGAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN NGRUKEM KECAMATAN MLARAK KABUPATEN PONOROGO - Nindya Arianulva Saksitasari; Hagus Muryanto; Raras Setyo Retno (UNIVERSITAS PGRI MADIUN, 2016)
This research aims to determine whether there is influence of quantum learning model with the audio visual media to science learning outcomes student class V SDN Ngrukem Mlarak District of Ponorogo in academic year 2015/2016. Due to very low yields Science learning and teachers teaching with conventional methods. This study uses a one-group pretest-posttest design. The research sample of 15 students and research instruments in the form of a multiple choice test. Datawere analyzed by using t-test. The result showed there are significant quantum learning model with audio visual media to science learning outcomes student class V SDN Ngrukem Mlarak District of Ponorogo in academic year 2015/2016.